Duplication of Right Ovarian Vein - Suresh Rao; Siva Konduru; T. Ramesh Rao (Archives of Current Research International, 2017)
We encountered a rare case of an anatomic variant of duplication of right ovarian vein in a 33 year old patient. Anatomic variant of the ovarian veins are extremely rare. However, with the increasing use of sophisticated diagnostic technology like computed tomography and magnetic resonance imaging these anatomical variant are more frequently diagnosed. The majority of venous anomalies are asymptomatic, however these variations can cause abnormal drainage, which could lead to clinical symptoms associated with the dysfunction of the vascular systems. Undiagnosed venous anomalies may lead to major complications during abdominal surgeries. Here we describe the detailed anatomical features of the area and discuss the related anatomical and developmental aspects.